The Geodesic Equations in a Two-Dimensional Finsler Manifold Equipped with a Matsumoto-Type Metric-II - Tripathi, Brijech Kumar; Chaubey, Vinit Kumar; Prajapati, Sejal (Armenian Journal of Mathematics, 2025)
This paper provides a comprehensive derivation of geodesic equations in a two-dimensional Finsler space characterized by a Matsumoto-type metric. It further explores the geometric applications of these equations on various surfaces, including cylinders, spheres, pseudo-spheres, and catenoids. Using illustrative examples and graphs, we analyze the geometric properties of geodesics for different parametric forms of these surfaces. The results enhance our understanding of geodesic behavior in Finsler geometry and shed light on curvature and geometric structures in diverse contexts.